STRAIN ANALYSIS IN SULAWESI BASED ON GPS DATA 2010-2022 - Luong Ayu, Sukma
Indonesia’s tectonic indicate high activity and caused deformation in the crust. Sulawesi is one of the largest islands that located in eastern Indonesia and has a complex geological structure. This is due to Sulawesi located at triple junction area. This research aims to calculate and analyze strain rates using daily deformation velocity data from GPS data. The data used comes from 54 GPS stations spread across Sulawesi. This data has been converted into daily solutions for each GPS station point owned by the Geospatial Information Agency (BIG). The average movement of Sulawesi is towards the northwest. The amount of settlement in southern Sulawesi varies between 1.1 cm/year to 3.61 cm/year. Central Sulawesi has large variations ranging from 1.1 cm/year to 4.5 cm/year and Southeast Sulawesi has 0.66 cm/year to 2.08 cm/year. The southern part of Sulawesi has 0.15 cm/year to 1.88 cm/year. The maximum strain rate for Sulawesi Island is 42.5 microstrain/year and the minimum strain rate is -26.84 microstrain/year. The dilatation rate of Sulawesi Island shows that there are areas experiencing large compression < -3 microstrain/year. The shear strain rate value is large, namely > 4 microstrain/year